1988
DOI: 10.7326/0003-4819-108-3-363
|View full text |Cite
|
Sign up to set email alerts
|

Botulism from Chopped Garlic: Delayed Recognition of a Major Outbreak

Abstract: Diagnosis of botulism in two teenaged sisters in Montreal led to the identification of 36 previously unrecognized cases of type B botulism in persons who had eaten at a restaurant in Vancouver, British Columbia, during the preceding 6 weeks. A case-control study implicated a new vehicle for botulism, commercial chopped garlic in soybean oil (P less than 10(-4)). Relatively mild and slowly progressive illness, dispersion of patients over at least eight provinces and states in three countries, and a previously u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…In our study, the observed clinical pictures agreed with published descriptions2* 4 7 [20][21][22][23] (table 111). The incubation period varied from 1 to 16 days.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the observed clinical pictures agreed with published descriptions2* 4 7 [20][21][22][23] (table 111). The incubation period varied from 1 to 16 days.…”
Section: Discussionsupporting
confidence: 82%
“…Cl. botulinum type B toxin was detected in faeces from one patient but not from patients' sera: in an outbreak of type B botulism associated with chopped garlic, toxaemia was only identified in 3 of 36 patients [15].…”
Section: Resultsmentioning
confidence: 99%
“…In this outbreak, several of the later cases had mild symptoms and the diagnosis of suspected botulism was not made on initial presentation [12]. It has been suggested in other reports that type B botulism progresses more slowly and is less severe than type A [14,15]. Cl.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis should be confirmed by toxin bioassay, although occasional falsenegatives can occur. Brain and spinal cord imaging may be required to exclude stroke, cord injury and tumour [12].…”
Section: Discussionmentioning
confidence: 99%